103k views
4 votes
Let g(x)=2x and h(x)=x^2+4. Find the value. (gh)(0)

User Dreamcrash
by
6.7k points

2 Answers

2 votes
What we do is to substitute to solve.

'(g(h(0)))

g(x) = 2x
g(h(x)) = 2 (x^2 + 4)
(gh)(0) = 2 (0^2 + 4) = 8
User Kiran Hegde
by
6.8k points
4 votes
If this is supposed to be multiplication, this is the answer.
(g*h)(0)
2x(x^2 + 4) =
2x^3 + 8x =
2(0) + 8(0) = 0

If this is supposed to be something else and you forgot the operator between the g and h, let me know and I will redo it for you.

User Sam Stephenson
by
6.2k points